El joven Hegel y la positividad de la religión cristiana - Méndez Sandoval, Carlos Andrés (Universidad de San Buenaventura - Cali, 2017)
Based on the analysis of the Hegelian concept of ‘Positivity’ presented in The positivity of Crhistian religion, and disclosing the historical perspective of the young philosopher on the subject matter, this article establishes both a historical and a philosophical reflections on the contemporaneous consequences of the Enlightenment’s propositions when the text was written (late 18th century). This double argument –on the one hand, the criticism about positivization of Christian religion based on an analysis of the past, and the updating of concept of positivity in the Enlightenment’s context- discloses the place of the young Hegel in 20th century’s theological and philosophical secularization.